2018
DOI: 10.1073/pnas.1809588115
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory discrimination of mRNAs by FMRP controls mouse adult neural stem cell differentiation

Abstract: Fragile X syndrome (FXS) is caused by the loss of fragile X mental retardation protein (FMRP), an RNA binding protein whose deficiency impacts many brain functions, including differentiation of adult neural stem cells (aNSCs). However, the mechanism by which FMRP influences these processes remains unclear. Here, we performed ribosome profiling and transcriptomic analysis of aNSCs in parallel from wild-type and Fmr1 knockout mice. Our data revealed diverse gene expression changes at both mRNA and translation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 48 publications
7
95
1
Order By: Relevance
“…Finally, FMRP (Fragile X Mental Retardation Protein), the loss of which is responsible for Fragile X syndromes, was shown to alter adult murine NSC differentiation capacities [97], mouse cognitive capacities [98], and human ESC neuronal differentiation [99]. Expression and ribosome profiling assays in murine wild type and Fmr1 KO NSCs revealed that loss of FRMP impairs both mRNA expression and translation of several neurogenesis and synaptic genes, and reduces the expression of 17 mitochondrial RP genes [100]. Interestingly, the drosophila FRMP represses translation by directly interacting with the 60S ribosomal subunit through RPL5 [101].…”
Section: Regulation Of Rrna Modificationsmentioning
confidence: 99%
“…Finally, FMRP (Fragile X Mental Retardation Protein), the loss of which is responsible for Fragile X syndromes, was shown to alter adult murine NSC differentiation capacities [97], mouse cognitive capacities [98], and human ESC neuronal differentiation [99]. Expression and ribosome profiling assays in murine wild type and Fmr1 KO NSCs revealed that loss of FRMP impairs both mRNA expression and translation of several neurogenesis and synaptic genes, and reduces the expression of 17 mitochondrial RP genes [100]. Interestingly, the drosophila FRMP represses translation by directly interacting with the 60S ribosomal subunit through RPL5 [101].…”
Section: Regulation Of Rrna Modificationsmentioning
confidence: 99%
“…As has been described before (33), several relationships between RPF and mRNA can be deciphered using ribosome profiling data. Because ribosomes are stalled in HD cells ( Fig.…”
Section: Global Ribosome Profiling Reveals Diverse Ribosome Occupancymentioning
confidence: 99%
“…Functions of FMRP have been reported to include regulation of translation, transport, and stability (De Rubeis and Bagni, 2010;Darnell et al, 2011;Ascano et al, 2012;La Fata et al, 2014;Pilaz et al, 2016;Liu et al, 2018). Although mechanisms are not fully elucidated at molecular and cellular levels, several FMRP mRNA targets are linked to various neurobiological processes such as neuronal migration and circuitry formation (La Fata et al, 2014), synaptogenesis (Darnell et al, 2011), DNA damage response (Alpatov et al, 2014), and epigenetic regulation (Korb et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we analyzed expression of ASD-related FMRP mRNA targets in the cortical primordium of Fmr1-KO by RT-qPCR. Only few studies have previously examined FMRP regulation on its targets at the mRNA level (Brown et al, 2001;Korb et al, 2017;Liu et al, 2018). These reports do not directly demonstrate the mechanistic role of FMRP on the transcription of its target genes, but they provide clues that mRNA levels are altered if FMRP function is impaired.…”
Section: Discussionmentioning
confidence: 99%